2022
DOI: 10.1038/s41467-021-27752-0
|View full text |Cite
|
Sign up to set email alerts
|

Competition between crystal growth and intracrystalline chain diffusion determines the lamellar thickness in semicrystalline polymers

Abstract: The non-equilibrium thickness of lamellar crystals in semicrystalline polymers varies significantly between different polymer systems and depends on the crystallization temperature Tc. There is currently no consensus on the mechanism of thickness selection. Previous work has highlighted the decisive role of intracrystalline chain diffusion (ICD) in special cases, but a systematic dependence of lamellar thickness on relevant timescales such as that of ICD and stem attachment has not yet been established. Studyi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 71 publications
1
42
0
1
Order By: Relevance
“…The simultaneous evaluation of these two parameters concluded that all samples completed the crystallization process at approximately 140°C, and the Al‐dross had no remarkable effect on the production rate of the plastic parts produced by injection molding. Finally, degree of crystallinity (X c ) of the samples were determined from the enthalpy values of melting obtained from the second heating run using the Equation ; Xnormalc%=ΔHnormalm1aΔHnormalmnormalox100 In the equation, Δ H m is the melting enthalpy change in the second heating (J g −1 ), ΔHnormalmnormalo is the melting enthalpy value of a 100% crystalline form of POM which is 326 J g −1 for POM [ 46 ] matrix polymer and α is the weight fraction of the filler. It was observed that the addition of 30% and 40% Al‐dross caused an increase in the amount of the crystalline structure, most likely because of the increased crystallization initiation temperature and longer crystallization time which allowed a longer time for the re‐organization of the polymer chain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The simultaneous evaluation of these two parameters concluded that all samples completed the crystallization process at approximately 140°C, and the Al‐dross had no remarkable effect on the production rate of the plastic parts produced by injection molding. Finally, degree of crystallinity (X c ) of the samples were determined from the enthalpy values of melting obtained from the second heating run using the Equation ; Xnormalc%=ΔHnormalm1aΔHnormalmnormalox100 In the equation, Δ H m is the melting enthalpy change in the second heating (J g −1 ), ΔHnormalmnormalo is the melting enthalpy value of a 100% crystalline form of POM which is 326 J g −1 for POM [ 46 ] matrix polymer and α is the weight fraction of the filler. It was observed that the addition of 30% and 40% Al‐dross caused an increase in the amount of the crystalline structure, most likely because of the increased crystallization initiation temperature and longer crystallization time which allowed a longer time for the re‐organization of the polymer chain.…”
Section: Resultsmentioning
confidence: 99%
“…In the equation, ΔH m is the melting enthalpy change in the second heating (J g À1 ), ΔH o m is the melting enthalpy value of a 100% crystalline form of POM which is 326 J g À1 for POM [46] matrix polymer and α is the weight fraction of the filler. It was observed that the addition of 30% and 40% Al-dross caused an increase in the amount of the crystalline structure, most likely because of the increased crystallization initiation temperature and longer crystallization time which allowed a longer time for the re-organization of the polymer chain.…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
“…Crystallization generally proceeds too fast to allow substantial resolution of entanglements at the growth front. 34 On the other hand, polymers with intracrystalline chain diffusion, so-called crystal-mobile polymers show crystal thickening during crystallization leading to crystallinities well-above 50% while the thickness of the amorphous regions is of similar size as in case of crystal-fixed polymers 11,32 . A resolution of entanglements in these systems could arise from intracrystalline chain diffusion.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The mechanical properties at small deformations are determined by the crystalline scaffold in the material leading to a high modulus that increases with crystallinity, whereas the existence of entanglements and tie molecules in the amorphous phase is responsible for strain hardening at large deformations and for toughness. [2][3][4][5] The factors governing the crystal thickness have been extensively studied, 2,[6][7][8][9][10][11] but the corresponding yet no less important question for the amorphous regions has obtained much less attention. While it has been suggested that the entanglements in the amorphous regions limit the crystallinity of polymers undergoing crystallization from the melt, 12,13 experimental evidence is inconclusive and the effects of the entanglements on the semicrystalline morphology are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…16,27,29,165 Crystal-amorphous interfaces, chain entangle-ments, random coils, kinks, and chain ends in polyethylene limit macroscopic thermal properties, which result in low thermal conductivity. 26,[166][167][168][169] The thermal conductivity in polymers may be crystallinity dependent. From the amorphous domains to crystalline domains, the thermal conductivity of semicrystalline polyethylene has been predicted to increase from 0.3 W m −1 K −1 to 50 W m −1 K −1 by molecular dynamics simulations.…”
Section: Thermal Conductivity Gap Between Theory and Experimental Mea...mentioning
confidence: 99%